An empirical investigation of the relation between performance measures: evidence from public enterprises in Korea / Tae-Sik Ahn, Kyoung-Joon Cho and Hyung-Rok Jung - Ahn, Tae-Sik; Cho, Kyoung-Joon; Jung, Hyung-Rok (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2006)
The information age environment requires that firms implement strategic performance measurement systems that focus on intangible assets. These systems are now widely used and implemented in the public sector. However, there have been few studies on the relationship between performance measures. Contingent factors and the management environment of the public sector are fundamentally different from the private sector. Consequently, performance measurement systems should be adapted before they are applied to the public sector. Using the data for 13 Korean public enterprises from 1990 to 2003, this study investigates the relation between performance measures. Our findings suggest that management measures are not significantly associated with goal achievement measures prospectively.